A formação dos professores dos cursos de direito no Brasil: a pós-graduação stricto sensu - Oliveira, Juliana Ferrari de (2010)
This study aimed at analysing the pedagogical development of Law university teachers in Brazil through its Master and Doctor`s degree courses. The declared objectives of such courses were analyzed as well as how they translate what they claim as objectives into their disciplines and programs. In order to do so, the data were collected from the Capes website based on the 2008 evaluation. Such evaluation contains data related to the program (PR), to its technical production (PT), to its disciplines (DI), to its proposal (PO), to its thesis and dissertations (TE), to its artistic production (PA), to its research lines (LP), to its teachers` performance (DA), to its bibliographic production (PB), to its teachers` curricula (CD), to its research projects (PP) and to its teachers` production (DP). The result was that among the 62 Law programs analyzed, 1) none of them contain research lines related to education; 2) 6 (10%) contain research projects with emphasis on teaching; 3) 15 (24%) produced thesis and dissertations about university teaching; 4) 41(66%) declared having, among their purposes, the aim of developing teacher education and 5) 34 (55%) offer pedagogical disciplines (with different number of hours). Concerning the teachers of the pedagogical disciplines, only 3 of the programs (11%) offer teachers with PhD in Education to teach the disciplines named as University Teaching Methodology. The study concluded that the Law university teacher development lacks attention and investment. At the end of this research, some proposals for thinking about Law teaching development are offered